ミズホキチ ニ オケル ヒョウシン ノ カンソク - 石沢, 賢二; イシザワ, ケンジ; Ishizawa, Kenji (1981)
P(論文) みずほ基地(72°42'S, 44°20'E, 海抜2230m)において氷震の観測が行われた。観測は1978年5月から翌年の1月までの長期間行われた。これにより氷震のおこる条件は, 気温と気温変化率との関数として表されることがわかった。そして発生の機構は雪をマックスウェル物体と仮定して説明された。氷震の震源の決定が行われた。P波の初動は観測システムのノイズにより判別できなかったので, 表面波の最大振幅が用いられた。この方法の妥当性は人工的震源によって発生させたP波と表面波の観測による震源計算によって確かめられた。ある群発氷震のうちの45個の氷震について震源が決定された結果, 震源はサーマルクラックのよく発達した"glazed surface"に集中した。このことにより, 氷震はサーマルクラックが発生するときの震動であることが証明された。震源の時間的移動に規則性はなく, "glazed surface"上のあらゆるところで無規則におこることがわかった。 The seismological observation of iceshocks was carried out at Mizuho Station (72°42'S, 44°20'E, 2230m a. s. l.), East Antarctica, during a period from May 1978 to January 1979. From the observation it was found that the condition of iceshock occurrence was expressed by a function of both the air temperature and the changing rate of the temperature. The iceshock occurrence was explained by the fracture of the surface snow which was assumed to be a Maxwell substance. The focus positions of 45 iceshocks of a swarm were calculated by using the observed velocity of surface wave. This calculation was checked by the result of an artificial hitting on the snow surface and was found to be efficient for the determination of the focus position. The result of the calculation indicated that the focus positions were concentrated at the glazed surface where snow accumulation did not take place for a long time (for example, 2 or 3 years) and the fracture cracks were observed. Therefore, it is concluded that the iceshocks are defined as a vibration caused by the fracture crack formation at the glazed surface due to a rapid decrease in the air temperature. departmental bulletin paper